Pengaruh Lingkungan Kerja Non Fisik, Kerjasama Tim, Kepuasan Kerja terhadap Kinerja Karyawan pada CV. Sumber Pinus Jaya Kediri - Naura Adhitya Qutrunnada; Edwin Agus Buniarto; Brahma Wahyu Kurniawan (Jurnal Riset Akuntansi, 2024)
This research aims to determine the influence of the non-physical work environment, teamwork, job satisfaction on employee performance at CV. Sumber Pinus Jaya Kediri. This type of research uses quantitative sampling techniques using a saturated sample method by taking all 45 members of the population. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination (R2) which were processed using the SPSS version 20 program. The research results concluded that partially the work environment Non-physical has a negative and significant effect on employee performance, with a significant t value of 0.000<0.05. Teamwork partially has a positive and significant effect on employee performance, with a significant t value of 0.000 <0.05. Job satisfaction partially has a positive and significant effect on employee performance, with a significant t value of 0.000 <0.05. The non-physical work environment, teamwork and job satisfaction simultaneously have a positive and significant effect on employee performance at CV. Sumber Pinus Jaya Kediri by looking at the significant F value of 0.000<0.05.